Literature Review: Challenges and Strategies For Implementing Digital Marketing Literacy in F&B Business Innovation in School Canteen Areas - Adelia Rahma; Imam Mukhlis; F. Danardana Murwani; Iva Khoiril Mala (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The global phenomenon shows rapid digital transformation in various sectors, including the food and beverage industry. At the local level, school canteen areas face challenges in following this trend, especially in implementing digital marketing literacy. This research aims to identify challenges and formulate effective strategies in implementing digital marketing literacy to support food and beverage business innovation in school canteens. The novelty of this research lies in its specific focus on the school canteen area, an area that is often overlooked in studies of digital literacy and business innovation. The urgency of this research is driven by the urgent need to increase the competitiveness and sustainability of the school canteen business through the adoption of digital technology. The method used in this research is Systematic Literature Review (SLR) by collecting relevant previous research through publish or publish then analyzing the article and narrowing it down regarding keywords. The research results show that although there are significant obstacles such as limited skilled human resources and access to technology, there are also great opportunities through increased training and digital capacity development. The implications of this research show that with the right strategy, school canteens can increase operational efficiency, consumer appeal, and ability to innovate, thus contributing positively to the educational ecosystem and student health.